1998
DOI: 10.1074/jbc.273.11.6373
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibitors Activate Stress Kinases and Induce Hsp72

Abstract: Inhibition of the major cytosolic protease, proteasome, has been reported to induce programmed cell death in several cell lines, while with other lines, similar inhibition blocked apoptosis triggered by a variety of harmful treatments. To elucidate the mechanism of proand antiapoptotic action of proteasome inhibitors, their effects on U937 lymphoid and 293 kidney human tumor cells were tested. Treatment with peptidyl aldehyde MG132 and other proteasome inhibitors led to a steady increase in activity of c-Jun N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
221
5
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(246 citation statements)
references
References 34 publications
17
221
5
3
Order By: Relevance
“…This result stands in variance to a recent report by Meriin et al, (1998). Their studies indicate that the catalytic activity of JNK1 can be stimulated in human U937 lymphoid tumor cells and human 293 kidney tumor cells.…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…This result stands in variance to a recent report by Meriin et al, (1998). Their studies indicate that the catalytic activity of JNK1 can be stimulated in human U937 lymphoid tumor cells and human 293 kidney tumor cells.…”
Section: Resultscontrasting
confidence: 94%
“…The most direct data implicating the requisite function of the JNK stress pathway in proteasome inhibitor-induced cell death comes from Meriin et al, (1998) who reported that ectopic expression of either a catalytically defective mutant version of JNKK (SEK1) or a transcriptionally incompetent c-jun protein blocks the cleavage of a co-expressed fragment of the U1 ribonucleoprotein. In this report cell death induction was not reported on a per cell basis (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To study the sensitivity of breast cancer stem-like cell to NF-κB pathway inhibitors, 11 compounds targeting different steps of the NF-κB pathway, including antioxidants Curcumin [32]; PDTC [33]; DETC [34]; Quercetin [35], NF-κB phosphorylation inhibitors Sulfasalazine [36]; Sulindac [37]; Ibuprofen [38]; PTL [39] and NF-κB degradation inhibitors MG-132 [40]; Cyclosporin A [41]; Genistein [42], were tested in this study. MCF7 sphere cells were used as a model of breast cancer stem-like cells [16,43].…”
Section: Ptl Pdtc and Detc Preferentially Inhibit Mcf7 Sphere Cell Pmentioning
confidence: 99%
“…For one possible explanation for these diverse effects, it was recently proposed that proteasome inhibitors activate c-Jun N-terminal kinase (JNK), which initiates an apoptotic programme, while they simultaneously induce Hsp72, which suppresses JNKdependent apoptosis. Consequently, a balance between these two effects might define the fate of cells exposed to the inhibitors (Meriin et al 1998). …”
Section: Biological Roles Of the Ubiquitinylationproteasome Directed mentioning
confidence: 99%